A study of threshold voltage fluctuations of nanoscale double gate metal-oxide-semiconductor field effect transistors using quantum correction simulation - Li, Yiming; Yu, Shao-Ming (My University, 2006)
In this paper, we computationally investigate fluctuations of the threshold voltage introduced by random dopants in nanoscale double gate metal-oxide-semiconductor field effect transistors (DG MOSFETs). To calculate variance of the threshold voltage of nanoscale DG MOSFETs, a quantum correction model is numerically solved with the perturbation and the monotone iterative techniques. Fluctuations of the threshold voltage resulting from the random dopant, the gate oxide thickness, the channel film thickness, the gate channel length, and the device width are calculated. Quantum mechanical and classical results have similar prediction on fluctuations of the threshold voltage with respect to different designing parameters including dimension of device geometry as well as the channel doping. Fluctuation increases when the channel doping, the channel film thickness, and/or the gate oxide thickness increase. On the other hand, it decreases when the channel length and/or the device width increase. Calculations of the quantum correction model are quantitatively higher than that of the classical estimation according to different quantum confinement effects in nanoscale DG MOSFETs. Due to good channel controllability, DG MOSFETs possess relatively lower fluctuation, compared with the fluctuation of single gate MOSFETs (less than a half of the fluctuation[-11pc] of SG MOSFETs). To reduce fluctuations of the threshold voltage, epitaxial layers on both sides of channel with different epitaxial doping are introduced. For a certain thickness of epitaxial layers, the fluctuation of the threshold voltage decreases when epitaxial doping decreases. In contrast to conventional quantum Monte Carlo approach and small signal analysis of the Schrodinger-Poisson equations, this computationally efficient approach shows acceptable accuracy and is ready for industrial technology computer-aided design application.
Keywords: Threshold voltage fluctuation; Random dopant; Quantum correction; Modeling and simulation; Double gate; MOSFET